2022
DOI: 10.1029/2021wr031856
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Hydrological Responses to Forest Expansion in Dry and Wet Basins of China: Implications for Future Afforestation Planning

Abstract: China has played a leading role in global greening efforts over the past few decades (Li et al., 2018;Zhu et al., 2016). Recently, the country sets a goal of achieving peak carbon and carbon neutrality by 2030 and 2060, respectively. This requires a systematic and nature-based strategy to offset anthropogenic carbon dioxide (CO 2 ) emissions. Enhancing China's carbon sink by planting forests in new areas is an appealing option. Afforestation is generally an effective way to sequester CO 2 and to improve enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 73 publications
0
5
0
1
Order By: Relevance
“…This indirectly confirms that compared to meteorological factors, changes in vegetation due to afforestation are the main factor affecting runoff in the Hunhe basin. Previous research has shown that water‐limited ecologically vulnerable basins are more sensitive to vegetation cover changes than other watersheds (Xue et al, 2022). In addition, vegetation can exhibit a sensitive response to climate change, including changes in precipitation, temperature, radiation, and other factors, showing significant spatial heterogeneity (Yang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This indirectly confirms that compared to meteorological factors, changes in vegetation due to afforestation are the main factor affecting runoff in the Hunhe basin. Previous research has shown that water‐limited ecologically vulnerable basins are more sensitive to vegetation cover changes than other watersheds (Xue et al, 2022). In addition, vegetation can exhibit a sensitive response to climate change, including changes in precipitation, temperature, radiation, and other factors, showing significant spatial heterogeneity (Yang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The Hunhe basin is a typical semiarid region in the Inner Mongolia section of the Yellow River, located in an ecologically vulnerable area with farming, forestry and animal husbandry intersecting (Bai et al, 2018; Feng, Liu, et al, 2022; Feng, Zeng, et al, 2022). The arid environmental conditions and limited resource supply greatly restrict the productivity and service functions of the ecosystem in the region, and the ecohydrological processes are sensitive to changes in the environment (Xue et al, 2022). The region experienced climate change and significant increases in vegetation greenness due to large‐scale afforestation programs (Yao et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evapotranspiration (ET) is an important part of the water cycle, linking energy, water, and circulation [1,2]. ET consumes more than 80% of the precipitation in arid and semi-arid regions and therefore plays a crucial role in the overall hydrological cycle [3][4][5][6][7]. It has been shown that ET is influenced by net radiation [8], wind speed [9], soil moisture stress [10], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Diversos estudos têm descrito que o reflorestamento pode contribuir com a redução das vazões mínimas, tendo em vista o incremento considerável da evapotranspiração, especialmente nos meses mais secos, em função do aumento da captação das águas subterrâneas pelas raízes profundas das florestas (RIBOLZI et al, 2018;AIRES et al, 2020;CECÍLIO et al, 2021). No entanto, trata-se de uma questão controversa, pois há grupos de estudiosos que defendem que as florestas possibilitam maior armazenamento de água no solo, dado ao sistema radicular profundo (XUE et al, 2022). Além disso, a distribuição espacial com que ocorre o reflorestamento também pode influenciar no comportamento das vazões.…”
Section: Comportamento Das Vazões Mínimasunclassified